On the understanding of zinc-oxide eugenol cement use prior to etch-rinse bonding strategies - Bezerra, Catarina Pires; Campos, Cristiano Fukugawa [UNESP]; Leite, Julio [UNESP]; Fernandes, Marina Struncová; Saraceni, Cintia Helena Coury; Rodrigues, Flávia Pires; Dutra-Correa, Maristela (Wolters Kluwer, 2019)
Context: Zinc-oxide eugenol (ZOE) is frequently used due to its satisfactory biological response, sedative effect on the pulp, and easy removal. However, literature is very controversial about the influence of the temporary cement-containing eugenol on the bond strength properties. Aims: This study aims to clarify the literature controversy by evaluating the bond strength of ZOE or ZOE-free applied before bonding procedures and the 7-day resting period after the first session. Settings and Designs: Twelve recently extracted third molars were randomly divided into three groups: Group 1: Control (without treatment), Group 2: Temp-Bond NE; Group 3: Temp-Bond. Subjects and Methods: After temporary restorations, the teeth were immersed in distilled water and stored for 7 days at 37°C. The temporary cement was mechanically removed, and prophylaxis was performed. The adhesive procedures were performed, and a 6-mm-high composite resin block was built. The teeth were immediately stored at 100% relative humidity at 37°C for 24 hours. Specimens with 0.7 (±0.2) mm2 of cross-sectional area were obtained and subjected to a microtensile bond strength (μTBS) test at 1 mm/min until failure. Statistical Analysis Used: Analysis of variance (ANOVA) and Tukey's post hoc test were used for statistical analysis. Results: ZOE or ZOE-free cement did not interfere in the μTBS between resin composite and dentine when used with a two-step-etch-rinse adhesive material, considering 7 days of resting period after the first session, by the ANOVA and Tukey's post hoc test (P < 0.05). Conclusions: The authors recommend the removal of the temporary cementation at least seven days after the first session and suggest that the clinicians follow-up further studies to use the cement in case its removal is recommended within a longer period.
Keywords: Dental adhesive; eugenol; microtensile test; resin composite; temporary cement